Evaluation of abnormal uterine bleeding: role of diagnostic hysteroscopy and its correlation with histopathology - Edwin, Rebecca; Vyas, Rupa C.; Shah, Sapana R.; Makwana, Shailesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective was to assess the accuracy of diagnostic hysteroscopy in evaluation of abnormal uterine bleeding and to correlate hysteroscopic findings with histopathology reports. Methods: A prospective study was carried out at our institute from January 2010 to December 2013. Ninety cases were included in this study. Patients’ age varied from 20 to 60. Those women with the history of abnormal uterine bleeding were admitted. In all cases diagnostic hysteroscopic examination and dilatation and curettage were carried out. Endometrium was sent for histopathology and correlation of hysteroscopic findings with histopathology reports was studied. Results: Various findings on hysteroscopy are as following: proliferative endometrium 36.66%, secretary endometrium 17.77% endometrial hyperplasia 24.44%, atrophic endometrium 5.55%, endometrial polyp 8.88%, submucous fibroid 4.44%, and endometrial carcinoma 2.22%. Conclusions: Hysteroscopy is an eye in uterus and it provides more accurate diagnosis than dilatation and curettage alone in patients with abnormal uterine bleeding.